Mathematical modeling of co-infection of HIV/AIDS and Pneumonia in Kenyan children - Odindo, David Onyinge (JOOUST Msc. Student, 2014)
The project aim at developing a mathematical model for HIV-Pneumonia co-infection showing the co-infection with treatment and determine mathematical significance of the developed model
Students' Project